A Study of Foliar and Soil Nutrient Status of Calligonum polygonoides Linn. At Churu (Rajasthan) - Sharma, B. M. (Indian Forester, 1966)
An ecological study of Calligonum polygonoides Linn. Has been described. The plant is a dominant shrub of the area. It has a better growth when growing in dune lows. This is followed by the sandy plains. Dune tops appeared to be comparatively unfavourable habitats. Distribution of the species has been given and the associates listed. The plant grows in coarse, sandy and alkaline soil. Results of soil analysis have been given to show the amount and behaviour of different cations at various depths. Root studies show that the plant has got very little branching. However, the proportion of root to shoot is considerable. Foliar analysis reveals that the plant is poor in minerals. An attempt has been made to determine the relationship between the mineral content of the leaves and quantity of available nutrients. It has been found that foliar sodium and phosphorus increase with a corresponding increase in the soil in these elements.